2020
DOI: 10.3390/su12051803
|View full text |Cite
|
Sign up to set email alerts
|

Dockless E-Scooter: A Green Solution for Mobility? Comparative Case Study between Dockless E-Scooters, Displaced Transport, and Personal E-Scooters

Abstract: This study applies a life cycle assessment (LCA) to the shared dockless standing e-scooter system that is established in Brussels. The results are given for four impact categories: global warming potential (GWP), particulate matter formation, mineral resource, and fossil resource scarcity. Regarding GWP, the use of the shared e-scooters in the current system causes 131 g of CO2-eq. per passenger-kilometer while the mode of transportation displaced has an impact of 110 g of CO2-eq. Thus, at present, the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
111
1
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(120 citation statements)
references
References 27 publications
2
111
1
6
Order By: Relevance
“…Furthermore, e-scooters are marketed as green solutions for urban traffic, even though empirical evidence supporting that claim is still scarce (Moreau et al, 2020), and results about electric vehicles illustrate a mixed picture. While recent investigations conclude that e-scooters cause slightly more CO2 emissions per kilometer compared to other modes of transportation (mainly due to their short lifespan, Hollingsworth et al, 2019;Moreau et al, 2020), others report that e-scooter usage could reduce emissions and congestion caused by automobiles (Allem and Majmundar, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, e-scooters are marketed as green solutions for urban traffic, even though empirical evidence supporting that claim is still scarce (Moreau et al, 2020), and results about electric vehicles illustrate a mixed picture. While recent investigations conclude that e-scooters cause slightly more CO2 emissions per kilometer compared to other modes of transportation (mainly due to their short lifespan, Hollingsworth et al, 2019;Moreau et al, 2020), others report that e-scooter usage could reduce emissions and congestion caused by automobiles (Allem and Majmundar, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although e-scooters are commonly seen as a green alternative to gasoline-powered motor vehicles, they present a number of environmental concerns—including greenhouse gas emissions, particulate matter formation, and use of mineral and fossil resources—that often go overlooked [ 44 , 45 , 46 , 47 ]. Findings from recent studies suggest that, overall, e-scooters have a more negative life cycle impact on the environment than the transportation modes they are replacing [ 2 , 47 ]. One study found that e-scooters’ impact on climate change is better than that of personal automobiles but worse than that of buses with higher ridership or electric bicycles [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study found that e-scooters’ impact on climate change is better than that of personal automobiles but worse than that of buses with higher ridership or electric bicycles [ 2 ]. With an average lifespan of about 2 years before often ending up in landfills, e-scooters’ high level of disposability is a key driver of negative environmental impacts, which means that this impact will likely lessen as technology improves, a goal e-scooter companies are actively workings towards [ 2 , 47 , 48 ]. Another major issue is the vehicles used to collect e-scooters each day for charging and relocating.…”
Section: Introductionmentioning
confidence: 99%
“…Results show an average carbon footprint equal to 126g CO2eq/pkt [26]. Dockless and private ES were also assessed for the city of Brussels on four midpoint indicators, using attributional LCA and the ReCiPe2016 characterization factors, reporting 131g of CO2eq/pkt for the shared version and 67g of CO2eq/pkt for the private version [27]. Even though the infrastructure is not integrated to the assessment of these two transportation modes, an integrated modal FFES LCA made in Paris reported smaller impacts -respectively 109 and around 60g of CO2eq/pkt -with the same IPCC 2013 factors but using the consequential version of the ecoinvent database [19].…”
Section: E-scooter Environmental Performancementioning
confidence: 99%